Social preference towards reactive aggression among justice-involved adolescents in Malaysia - Ng, Eng Eng; Daud, Mohd Najmi; Arshat, Zarinah; Dahamat Azam, Naqi (Human Resource Management Academic Research Society, 2020)
Low social preference has been found to produce aggression as a maladaptive outcome and response among adolescents. However, it is not clear whether the factors of social preference contribute to aggression. Therefore, the present study investigates whether the factors of social preference, namely, insult, ignorance, accusation, and physical attacks/bossiness, predict reactive aggression. Using cluster sampling, questionnaires were administered to 183 juveniles enrolled in government-approved schools in four geographical regions throughout West Malaysia. Data gathered was then analyzed via the Structural Equation Modelling-Analysis of a Moment Structures (SEM-AMOS) Version 23.0 approach. Findings showed all factors significantly and positively predicted reactive aggression. Future studies should implement diverse and well-defined measures to better understand how social preference can determine reactive aggressive behaviors. Implications of imitating the aggressive behaviors of other adolescents, internalizing aggressive victimization experiences, forming of healthy peer support from non-deviant socialization as an intervention, and implementing early intervention during adolescent development were discussed.